Implementation of religious and cultural tourism development policies in Penyengat island - Suhaila, Raja; Baijuri, Raja Hamidah Teja (Indonesian Tourism Journal, 2024)
The tourism development program on Pengenyat Island, Tanjungpinang City has been running with the aim of increasing public awareness about the importance of culture and religion. The aim of this research is to analyze the policy implementation model using Meter & Horn (1975) theory. This research method uses a descriptive-qualitative approach by studying related documents and conducting interviews with relevant informants. Data analysis uses triangulation techniques which are analyzed in depth. The research results show that the tourism development program on Penyengat Island has made a positive contribution to tourism development. Model in the Implementation Process of Meter & Horn (1975) Development Policy for Tourism Development on Penyengat Island on Policy Standards and Targets requires continuous evaluation and improvement, then resources are carried out such as training and increasing insight into both human resources and natural resources. The characteristics of the Implementing Organization have the potential to increase cooperation with the government and other related parties. Next, Inter-Organizational Communication is related to institutional capacity in decisions on Development Programs so that the importance of community participation in monitoring, then the Disposition or Attitude of the Implementer and the Implementing Activities that have been carried out must pay attention to the importance of the government playing an active role by paying attention in the early stages of the plan, providing guidance and education to the community . Finally, socio-economic and political environmental conditions need to pay attention to the customs and cultural awareness of local communities that must be maintained in the policy implementation process. The conclusion of this research is that local governments need to increase public awareness about the importance of culture and religion through Tourism Development programs that are in accordance with local culture and traditions.